Estilos de vida en tiempos de pandemia - Maguiña Concha, Ana Elizabeth (2021)
The pandemic negatively affects human life in all its aspects, lifestyles are affected due to the compulsory confinement experienced in the initial months and the social restrictions that remain until today, before this there is a greater stay at home which affects the practicing physical activity and eating, having an impact on physical and emotional health.